Social Commerce Adoption among MSME in Kuwait: The Role of Perceived Value and Organizational Innovation - Omar M.A.; Sulaiman R.B. (Natural Sciences Publishing, 2025)
Growing internet usage presents chances for MSME to develop their businesses particularly in social media and e-commerce. This research examines how technological, organizational, and environmental factors affect Kuwaiti Micro Small, and Medium Enterprises (MSME) adoption of social commerce (s-commerce). The study also examines the mediating role of perceived value and the moderating role of organizational innovation. Data was collected from such as complexity, compatibility, and relative advantage affected positively the S-commerce usage. In addition, organizational factors such as top management support, organizational readiness, and cost significantly affect e-commerce usage. Environmental factors such as external pressure and governmental support are substantial predictors of S-commerce usage. Perceived value mediated the effect of technological and organizational factors on S-commerce usage while organizational innovation moderated the impact of technological factors on S-commerce usage. This study guides MSMEs through the changing terrain of s-commerce adoption by synthesizing theoretical and practical findings, laying the groundwork for informed decision-making and future research and benefits to MSMEs. ? 2024 NSP Natural Sciences Publishing Cor.